Syaikhona Muhammad Kholil: Motif Perjuangan melalui Pendidikan, Karya dan Pesantren - Ahmad Ahmad; Humaidi Humaidi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
Syaikhona Mohammad Kholil Bangkalan is one of the great Ulama’s figures. Syaikhona Mohammad Kholil Bangkalan is said as the teacher of the teachers. One of the biggest roles of Syaikhona Mohammad Kholil Bangkalan was his central role in establishing Nahdlatul Ulama'. This research method was historiography research. The technique in this study used documentation techniques in the form of primary sources of manuscripts and relevant references. This research data analysis used descriptive-interpretative In conclusion, the relationship between Syaikhona Mohammad Kholil 's struggle in nationalism and the independence of the Indonesian nation was aplied through education, book, and Islamic boarding schools. Syaikhona Mohammad Kholil choose the patterns and strategies to pursue education, work and Islamic boarding schools are conscious choices. This conscious choice is based on the analogy of the example of preaching carried out by the Prophet Muhammad. the Prophet Muhammad was preached the Islamic struggle, through strengthening the spirit of ideology in faith, Islam and Ihsan.